WASHBACK OF ENGLISH NATIONAL EXAMINATION IN THE INDONESIAN CONTEXT - Furaidah, Furaidah; Saukah, Ali; Widiati, Utami (TEFLIN Journal, 2015)
This study examines how teachers teach English to prepare students for high-stakes English national examination in the Indonesian context. Data were collected from two high-achieving and three low-achieving schools with eleven teachers as the subjects of in-depth interviews and nonparticipatory classroom observations. The findings reveal that bi-directional washback was found in both groups of schools. The schools of low achievers were found to have more intensive negative washback than those of high achievers. The different intensity of negative washback is likely related to the teachers' perspective about their students' level of competence for passing the national examination and about the quality of their schools. The consistently unsatisfactory national examination scores of the low-achieving schools, despite their concerted efforts in the examination preparation program, suggest that the government should focus on supporting such schools with more empirically-based empowerment programs, which would become an indispensable follow-up actions regarding the implementation of the highstakes national examination.